2020
DOI: 10.1186/s12877-020-01928-7
|View full text |Cite
|
Sign up to set email alerts
|

Delirium is associated with high mortality in older adult patients with acute decompensated heart failure

Abstract: Background Delirium is associated with high mortality after cardiac surgery. However, evidence on the epidemiology of delirium in patients with acute decompensated heart failure (ADHF) is limited. This study aimed to assess the incidence and prognostic impact of delirium in patients with ADHF. Methods This single-center prospective observational study enrolled 132 consecutive patients with ADHF. We utilized the Diagnostic and Statistical Manual of Mental Disorders, fifth edition and classified the patients in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…While a few prior studies have assessed the prevalence and outcomes of delirium in HF patients, all of those were small single-center analyses. [22][23][24][25] Our study confirms the association of delirium with higher mortality in a much larger population of HF patients using the NIS sample which is much more diverse and representative. The prevalence of delirium was much lower in our study reaching approximately 1.6% in 2014 compared to 8-23% in various studies on HF patients and patients admitted to the coronary ICU.…”
Section: Discussionsupporting
confidence: 77%
“…While a few prior studies have assessed the prevalence and outcomes of delirium in HF patients, all of those were small single-center analyses. [22][23][24][25] Our study confirms the association of delirium with higher mortality in a much larger population of HF patients using the NIS sample which is much more diverse and representative. The prevalence of delirium was much lower in our study reaching approximately 1.6% in 2014 compared to 8-23% in various studies on HF patients and patients admitted to the coronary ICU.…”
Section: Discussionsupporting
confidence: 77%
“…However, cognitive impairment is a broad term that encompasses both acute (delirium) and chronic (dementia) cognitive deficits, which in the context of an acute illness, may have different therapeutic and prognostic significance. Previous studies similarly observed that delirium was associated with increased risk of rehospitalization, nursing home placement, and death in hospitalized AHF patients [11][12][13][14][15]. However, most were single-center studies that enrolled older patients (average age range: 75 to 83 years old) who were predominantly White or Asian race.…”
Section: Plos Onementioning
confidence: 99%
“…Importantly, most delirium studies exclude adults who are less than 65 years old [5,6]. The average age of previously published AHF and delirium outcome studies ranged from 75 to 83 years old [11][12][13][14][15]. Younger patients with AHF may similarly be susceptible to developing delirium and adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that delirium is a common symptom of HF patients and is associated with increased mortality, prolonged hospital stays, and heightened medical costs. Delirium seriously affects the health and QoL of patients and imposes a heavy burden on medical resources (16)(17)(18)(19)(20)(21)(22)(23). It was reported that HF is an independent risk factor for delirium (24).…”
Section: Introductionmentioning
confidence: 99%